Speech Acts Analysis in Album Song’s Lyrics by Osen Hutasoit - Grace Siagian, Anselia; Nur Hadi, Muhammad; David Marudut Silalahi, Charles (Journal of Comprehensive Science, 2025)
Songs are a combination of words and melodies that serve as a medium for expressing emotions and messages. This study examines the speech acts present in the lyrics of "Ganjang Ma Umurmi" by Osen Hutasoit, focusing on the role of language in shaping meaning and emotional depth. The research aims to analyze the different types of speech acts found in the song lyrics, including assertive, declarative, expressive, and commissive illocutionary acts, as well as locutionary acts. This study employs a qualitative descriptive method, integrating literary analysis to explore the linguistic features and their implications in the song’s lyrics. Data was collected through literature review and analyzed using a pragmatic approach to identify speech act classifications. The results reveal 15 illocutionary acts, covering assertive, declarative, expressive, and commissive types, along with 8 locutionary acts. These speech acts contribute significantly to the song’s storytelling, enhancing its emotional and communicative impact. In conclusion, "Ganjang Ma Umurmi" serves as an excellent example of how speech acts function in artistic expression. The study highlights the importance of linguistic elements in conveying emotions, cultural values, and personal reflections in song lyrics, making it a valuable reference for further research in pragmatics and literature.